2020
DOI: 10.3389/fchem.2020.00570
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Cross-Linked Cellulose Nanocrystal Aerogels for Effective Removal of Cation Dye

Abstract: In this study, porous aerogels were prepared by directional freeze-drying via cross-linking cellulose nanocrystals (CNCs) with poly(methyl vinyl ether-co-maleic acid) (PMVEMA) and poly(ethylene glycol) (PEG). The thermal properties and physical adsorption performance toward cation methylene blue dye of the obtained CNC aerogels were investigated. The maximum degradation temperature was increased from 324°C of CNCs to 355°C of cross-linked CNC aerogels. The dye adsorption isotherm results showed that the maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 55 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…The peaks observed at 1715 cm −1 of untreated sample can be due to both the ester linkage and the untreated carboxylic acid groups. In the NaOH treated sample, the peak at 1589 cm −1 was attributed to the carboxylate formed because of the neutralization of the unreacted carboxylic acid groups and the sodium hydroxide, and the remaining signal at 1715 cm −1 solely confirmed the establishment of ester cross-linkages between cross-linker and CMC/GO, which were previously reported by Goetz et al [ 27 , 31 ].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The peaks observed at 1715 cm −1 of untreated sample can be due to both the ester linkage and the untreated carboxylic acid groups. In the NaOH treated sample, the peak at 1589 cm −1 was attributed to the carboxylate formed because of the neutralization of the unreacted carboxylic acid groups and the sodium hydroxide, and the remaining signal at 1715 cm −1 solely confirmed the establishment of ester cross-linkages between cross-linker and CMC/GO, which were previously reported by Goetz et al [ 27 , 31 ].…”
Section: Resultssupporting
confidence: 74%
“…The highly organized structures in the achieved foams exhibited enhanced mechanical performance and showed excellent water stability. After that, the authors used the foams for MB adsorption [ 31 ], and it showed excellent adsorption capacity, structure stability and reuse performance.…”
Section: Introductionmentioning
confidence: 99%
“…The development of alternative adsorption materials with high adsorption capacity, high selectivity, and easy regeneration is required for practical application. In the present study, a number of nonconventional and low-cost adsorbents based on biopolymers Yang et al (2021) , cellulose Liang et al (2020) , alginate and agricultural wastes, such as garlic peel Asfaram et al (2014) , peanut husk Sadaf and Bhatti. (2014) , orange peel Munagapati et al (2019) , peach gum Zhou et al (2014) , and pomelo peel Argun et al (2014) , were exploited for the effective removal of dyes from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The MCMFCs had a maximum adsorption capacity of MB at 303 mg/g [ 65 ]. Porous cellulose nanocrystal aerogels fabricated by cross-linking with poly (methyl vinyl ether-co-maleic acid) (PMVEMA) and poly(ethylene glycol) (PEG) were tested for the removal of methylene blue (MB) by Liang et al [ 66 ]. They reported a maximum adsorption capacity of 116.2 mg/g for the CNC-derived polymeric adsorbent (CNC/PMVEMA/PEG) with a similar performance over five adsorption/desorption cycles.…”
Section: Biopolymer-based Dye Removal Technologiesmentioning
confidence: 99%
“…CuO oxide nanowires incorporated chitosan (CS) and polyvinyl alcohol (PVA) polymeric nanocomposite (CS-PVA@CuO) were used for the removal of Acid Blue 25 (AB25) with an adsorption capacity of 171.4 mg/g [ 76 ]. Table 2 summarizes some of the recent dye removal studies carried out using cellulose, chitin and chitosan-derived adsorbents [ 25 , 26 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Generally, the adsorption capacity of an adsorbent is governed by the source and the surface properties such as porosity and surface area.…”
Section: Biopolymer-based Dye Removal Technologiesmentioning
confidence: 99%